PENYELESAIAN PINJAMAN BERMASALAH DALAM PROGRAM PINJAMAN DANA BERGULIR UNIT PENGELOLA KEGIATAN (UPK) PNPM MANDIRI PERDESAAN KELOMPOK SIMPAN PINJAM PEREMPUAN (SPP) DI KECAMATAN KARANG BARU KABUPATEN ACEH TAMIANG DITINJAU DARI PERSPEKTIF KITAB UNDANG-UNDANG - Iqbal Mursalin; Tan Kamello; Yefrizawati Yefrizawati; Rosnidar Sembiring (USU LAW JOURNAL, 2017)
ABSTRACT The Implementation of the revolving fund by CGU is part of PNPM MP that aims to improve the economic welfare of the family in the countryside. It also dilakuakn in KarangBaru where the majority of the population who are women just graduated from high school, but the system of revolving funds in UPK with the communities do not have a clear legal position on the legislation in Indonesia. Based on the above background found the problem: First, lending procedures revolving fund UPK to the SPP in KarangBaru district of Aceh Tamiang viewed from the perspective of the draft Civil Code, two factors that cause bad loan revolving fund UPK against group SPP in KarangBaru district of Aceh Tamiang, completion of non-performing loans in the UPK program revolving fund against the SPP in KarangBaru sub-district of Aceh Tamiang viewed from the perspective Seen from the perspective of the Book of the Law of Civil Law.   Keywords : Settlement, Troubled Loan, Revolving Fund, UPK